Artificial Intelligence and Evolutionary Computations in Engineering Systems Proceedings of ICAIECES 2015 - Dash, Subhransu Sekhar; Bhaskar, M. Arun.; Panigrahi, Bijaya Ketan; Das, Swagatham; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in the first International Conference on International Conference on Artificial Intelligence and Evolutionary Computations in Engineering Systems (ICAIECES -2015) held at Velammal Engineering College (VEC), Chennai, India during 22 - 23 April 2015. The book discusses wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of Communication, Computing and Power Technologies.
Design Specifications of Reversible Logic Using CMOS and Quantum Dot Cellular Automata -- Chapter 89. Effective Models for Segmentation and Shape Tracking of Cells -- Chapter 90. Real Time Rule Based Scheduling System for Integrated Delivery in a Semiconductor Manufacturing Using Evolutionary Algorithm Based Simulation Approach -- Chapter 91. Least Square Mean Optimization Based Real Object Detection and Tracking -- Chapter 92. Improving Efficiency and Fairness in Mobile AD HOC Networks -- Chapter 93. A Novel Content Based Image Indexing and Retrieval Framework Using Clock Wise Local Difference Binary Pattern (CWLDBP) -- Chapter 94. Self-organization Strategiesfor Hierarchical network structure in Wireless Ad-Hoc Networks: A Short Survey -- Chapter 95. Efficient Fused Architectures for FFT Processor Using Floating Point Arithmetic -- Chapter 96. Design, Test and Evaluation of Trace-Buffer Inserted FPGA System -- Chapter 97. Mining Based Device Control for Home Automation -- Chapter 98. Methods and Materials for Adsorbing the Benzene Molecule Based on MEMS -- Chapter 99. A Multi Parametric Hybrid Cooperative Localization Scheme for Mobile Communication Network -- Chapter 100. Interface and Control of Appliances by the Analysis of Electrooculography Signals -- Chapter 101. An Advanced Magnetic Resonance Imaging Technique for Detection of Abnormal Changes Using Artificial Neural Network -- Chapter 102. Implementation of a Hybrid Renewable Energy Plant with Remote Monitoring Feature -- Chapter 103. Artificial Neural Network Control Strategy for Mul.
Keywords: Computational intelligence; Artificial intelligence; Algorithms; Computational Intelligence; Artificial Intelligence; Algorithms